Green, blue and economic water productivity: a water footprint perspective from the Upper Awash Basin, Central Ethiopia - Birtukan Abebe Hirpa; Girma Berhe Adane; Asfawossen Asrat; Dessie Nedaw (Journal of Water and Climate Change, 2023)
The rise in global freshwater consumption, inefficient water use and population growth are the main drivers of water scarcity and food insecurity. This study analyzed the green, blue and economic water productivity (GWP, BWP and EWP, respectively) of the rainfed (teff, maize and sorghum) and irrigated (sugarcane) crops along with green water scarcity (GWS) in the Upper Awash Basin using water footprints (WFs) approaches. Teff has the lowest average GWP (∼0.3 kg/m3) and the highest average WF (4205 m3/ton) between 2000 and 2010 with an average EWP of ∼0.3 USD/m3 which is higher than those of other rainfed cereal crops (maize and sorghum). The highest GWS of maize was recorded in Metehara (269 mm/growing period) and the lowest in Debrezeit (70 mm/growing period) with an intermediate value of 90 and 117 mm in Wonji and Melkassa, respectively. All the rainfed crops have lower EWP (less than 0.3 USD/m3) compared with the irrigated sugarcane in the basin. This study demonstrates that increasing the value per unit of green/blue water through increasing yield per unit of supply and switching from high to low WFs crops has significant implications for addressing the water scarcity problem by setting a WP benchmark in the basin. HIGHLIGHTS Green, blue and economic water productivity (WP) of crops was examined.; Eastern Upper Awash Basin depicted more green water scarcity than the western parts.; Teff has the lowest green WP compared with maize and sorghum.; Rainfed crops have lower economic WP than irrigated sugarcane.; This water footprint approach in quantifying WP can be used to establish the WP benchmarks in similar water-stressed basins in the world.;